2001
DOI: 10.3233/jad-2001-3502
|View full text |Cite
|
Sign up to set email alerts
|

Characterization by atomic force microscopy and cryoelectron microscopy of tau polymers assembled in Alzheimer's disease1

Abstract: The structure of the Paired Helical filaments (PHF) 1 , a polymer of the microtubule associated protein tau, has been studied by Atomic Force Microscopy (AFM) and by cryoelectron microscopy. Mica and graphite were used as substrates in the AFM analysis with no differences in the results. A banding pattern of 8-12 nm width within the helical structure is found when detailed analysis of the data is performed. High AFM resolution images obtained by using an ultra sharp tip confirm the previous results and sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 49 publications
4
20
1
Order By: Relevance
“…Comparing the periodicity and thickness of thick Tau fibrils characterized here by AFM with the periodicity of ϳ80 nm and width of ϳ22 nm reported for PHFs by EM (13,14), it may be concluded that the thick Tau fibrils reflect the commonly reported PHF structure. This interpretation would be in agreement with previous AFM studies (17,35). However, the coexistence of thin smooth, thin corrugated, and thick fibrils reassembled from the same Tau proteins suggests that these different structural classes may be gathered from Tau proteins showing different assemblies or conformations.…”
Section: Tau Proteins Assemble Into Polymorphoussupporting
confidence: 93%
“…Comparing the periodicity and thickness of thick Tau fibrils characterized here by AFM with the periodicity of ϳ80 nm and width of ϳ22 nm reported for PHFs by EM (13,14), it may be concluded that the thick Tau fibrils reflect the commonly reported PHF structure. This interpretation would be in agreement with previous AFM studies (17,35). However, the coexistence of thin smooth, thin corrugated, and thick fibrils reassembled from the same Tau proteins suggests that these different structural classes may be gathered from Tau proteins showing different assemblies or conformations.…”
Section: Tau Proteins Assemble Into Polymorphoussupporting
confidence: 93%
“…In summary, our results obtained with acrolein and methylglyoxal suggest that the formation of covalently linked dimers, trimers, or tetramers may be an important step in filament assembly (17,55,56). Consistent with such a suggestion, a Tau tetramer was previously suggested as the smallest building block of AD-derived PHFs when PHF images were analyzed quantitatively from atomic force microscopy and electron microscopy (54).…”
Section: Microscopic Fibrilssupporting
confidence: 63%
“…6) show some resemblance to PHFs isolated from AD brains (1). These AD filaments are ϳ530 nm long with characteristic subunits of ϳ16 ϫ 82 nm (54). However, our synthetic filaments are similar but are straight and lack the twisted appearance of the PHF isolated in vivo.…”
Section: Microscopic Fibrilsmentioning
confidence: 71%
“…The beads on a string morphology of the filaments revealed by AFM is in contrast with the morphology of other filament-like structures found in other neurodegenerative diseases like the paired helical filaments isolated from Alzheimer's disease patients, which present a clear helical and ribbon-like morphology (Pollanen et al, 1994;Moreno-Herrero et al, 2001. However, the beads on a string morphology of the here purified filaments is identical to that reported after in vitro assembling of recombinant exon 1 mutant htt (Poirier et al, 2002) and very similar to those generated by other amyloidogenic proteins such as A␤, ␣-synuclein, and yeast (prion) Sup35 NM peptide (Harper et al, 1999;Rochet et al, 2000).…”
Section: Discussionmentioning
confidence: 69%
“…The sample was washed with deionized and double-distilled water, dried with nitrogen gas, and imaged in air with a commercial microscope (Nanotec Electronica, Madrid, Spain) operating in noncontact dynamic mode as previously described (Moreno-Herrero et al, 2001. Images were processed using WSxM freeware.…”
Section: Atomic Force Microscopy Of Purified Aggregatesmentioning
confidence: 99%